ANALISIS KEPATUHAN PEMILIK RUMAH KOS DALAM MEMENUHI KEWAJIBAN PAJAK HOTEL DI KELURAHAN KLEAK KECAMATAN MALALAYANG - Apita, Grisela Vivi; Pangemanan, Sifrid S.; Warongan, Jessy D.L (GOING CONCERN : JURNAL RISET AKUNTANSI, 2019)
One of the biggest local sources of regional income in Regional Original Revenue (PAD) is from the tax and retribution sector, where taxes are mandatory contributions that must be paid to the state. Tax payments have never been spared from various problems, one of which is the problem of compliance from taxpayers to fulfill obligations in paying taxes. The problems in this study include: (1) how the compliance of boarding house owners in meeting hotel tax obligations, (2) what are the obstacles in fulfilling boarding house owner compliance in meeting hotel tax obligations. The purpose of this study is to: (1) determine the compliance of boarding house owners in meeting hotel tax obligations, (2) constraints in fulfilling homeowner's compliance in meeting hotel tax obligations. The analytical method used in this research is descriptive qualitative in which the purpose of each data collected is analyzed then drawn conclusions descriptively. The results obtained from this study are that boarding house owners have not complied in fulfilling their hotel tax obligations, obstacles that affect the compliance of boarding house owners, among others: awareness of taxpayers, tax knowledge and understanding, tax socialization, and service tax. Boarding house owners are expected to increase awareness of their taxex so they can carry out their obligations as taxpayers.